Guiding biological control of alligator weed by Agasicles hygrophila (Coleoptera: Chrysomelidae) at macroscale: where are the potential global areas suitable to apply it and how it can change in climate change scenarios. - Pulzatto, Mikaela Marques (2022)
Invasive species can have many negative impacts on the biodiversity, ecosystem services, human health and the economy, and therefore need to be managed. An amphibious weed of global importance, Alternanthera philoxeroides, and the macroecological patterns of its biological control were evaluated using one of its main specialist herbivores, Agasicles hygrophila. This was considered the first successful case of biological control of an aquatic plant, although it is not equally effective on a global scale. Due to their different environmental tolerances and the greater phenotypic plasticity of the plant, the distribution of both species do not always overlap in the globe, creating geographic variability in the efficiency of biocontrol. The first approach was to analyze the current global potential distribution of A. philoxeroides and A. hygrophila to seek the areas of overlaps and gaps between them. The overlapping areas would be the most relevant for using A. hygrophila as alligator weed biological control in the globe. However, in response of climate change, it seems that the alligator weed is worryingly spreading across the globe, which can worsen in future scenarios and alter its distribution in the next decades. The second approach evaluated the effects of climate change on the global distribution of A. philoxeroides and A. hygrophila. New distribution areas for both species in future global warming scenarios and new overlapping and non-overlapping areas across the globe were identified. Species Distribution Models (SDMs) were applied in both chapters to predict the potential distribution of the two species in present and future scenarios considering different environmental predictors in each one. Currently, the southeast coast of the USA, southeast China and New South Wales, Australia are the most favorable areas in the world to apply alligator weed biocontrol, while the west coast and mid-latitudes in the east of the USA and the eastern Australia are not favorable. The results were corroborated by reports in the literature that demonstrated successful control in overlapping areas and failures in non-overlapping areas of the models’ distributions. However, while general geographic patterns will hold in future scenarios, it is predicted a major northward expansion of the alligator weed, but not of the insect, especially in the USA, Canada, Europe, China, South Korea and Japan, which will create a new zone of low or no control efficiency at higher latitudes. These macroecological patterns will help direct efforts to apply the biological control for the alligator weed not only today, but also in future climate change scenarios.